1999
DOI: 10.1046/j.1365-2826.1999.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Long‐Term Treatments with the Selective Serotonin Reuptake Inhibitor Citalopram Modulate the HPA Axis Activity at Different Levels in Male Rats

Abstract: It is well established that the maximal therapeutic effect of selective serotonin reuptake inhibitors (SSRI) are achieved in depressive patients after several weeks of treatment, but the adaptive processes leading to the therapeutic effects are unclear. It has been shown that hyperactivity in the hypothalamic-pituitary-adrenal (HPA) axis in depressive patients is affected by long-term antidepressant treatment. These changes occur in association with the mood normalising effect, suggesting that antidepressants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 38 publications
5
58
0
2
Order By: Relevance
“…Previous studies have reported that basal PVN CRF mRNA is decreased by 30 to 67% (Brady et al, 1991(Brady et al, , 1992Aubry et al, 1999) or is unchanged (Jensen et al, 1999) after chronic antidepressant treatment. Consistent with the latter study, we found that administration of a variety of antidepressant agents produced no effect on basal CRF hnRNA or mRNA expression in the PVN.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have reported that basal PVN CRF mRNA is decreased by 30 to 67% (Brady et al, 1991(Brady et al, , 1992Aubry et al, 1999) or is unchanged (Jensen et al, 1999) after chronic antidepressant treatment. Consistent with the latter study, we found that administration of a variety of antidepressant agents produced no effect on basal CRF hnRNA or mRNA expression in the PVN.…”
Section: Discussionmentioning
confidence: 89%
“…Larson and Summers (2001) showed that a 1-week treatment with the SSRI, setralin, reduces aggressive behaviour and reverses dominant social status in the lizard Anolis carolinensis. As seen with elevated dietary intake of TRP, short-term treatment with SSRI activates the HPA axis, whereas long-term treatment has the opposite effect, desensitising the HPA axis in rats (Jensen et al, 1999). An effect on the densities and transduction mechanisms of postand/or pre-synaptic 5-HT receptors, resulting in a delayed elevation of 5-HT post-synaptic effects in certain brain regions, has been suggested as a mechanism involved in mediating the effects of long-term SSRI treatment (Mongeau et al, 1997;Nutt et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies on the effects of the chronic administration of different antidepressants demonstrate that a decrease of the HPA-axis activity is a final common pathway of antidepressant effects, but that the different antidepressants unfold their specific pharmacological efficacy on varying HPA-axis levels and receptor subsystems. Tricyclic antidepressants as well as the SSRI fluoxetine are likely to increase either GR m-RNA or MR m-RNA expression in the hippocampus, depending on the type of drug (Barden et al, 1995;Brady et al, 1992;DeRijk et al, 2001;Holsboer and Barden, 1996;Jensen et al, 1999;Okugawa et al, 1999;Seckl and Fink, 1992). Owing to the increase of hippocampal MRs and GRs, they are thought to regain their balance re-establishing the inhibitory tone on the PVN in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%